Adaptation of residential houses to increasing wind hazard under climate change - Nishijima, Kazuyoshi; ICASP14; Tomokiyo, Eriko (My University, 2023)
Adaptation to climate change has become a central issue all over the world. Japan is facing increasing wind damage to residential houses due to the impacts of more frequent intensified typhoons. However, the adaptation of residential houses in Japan is not straightforward because of multiple reasons. One of such reasons concerns existing residential house stock and it is that the damage to houses by wind in Japan typically do not extend to total or structural failures and thus the damaged houses are repaired as those were. Consequently, wind vulnerable houses remain wind vulnerable. A reasonable way to mitigate increasing wind risk should be, therefore, to motivate owners of houses damaged by wind to decide to repair with higher wind-resistant performance, hereafter, it is called upgraded repair; in addition to the adaptation of the design code to increasing wind hazard and the usual retrofit of houses before damage. This study investigates the effectiveness of upgraded repair strategy under various scenarios and conditions. First, regional wind vulnerability models for residential houses are built based on existing literature on wind vulnerability as well as exposure data available. Second, a simplified wind hazard model is developed based on the wind hazard map implied in the design code of Japan and a wind pressure database. On these bases, assuming (a) several scenarios on the change of the wind hazard due to climate change, (b) the minds of the owners toward upgraded repair and (c) background renewal and retrofit of existing houses, the changes of the wind risk over time are simulated and analyzed. The obtained results and discussion facilitate, among others, policymakers to make decisions on the allocation of limited budget in order to effectively mitigate future wind risk.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED